A novel use of HIV surveillance and court data to understand and improve care among a population of people with HIV experiencing criminal charges in North Carolina 2017–2020 - Elizabeth C. Arant; Andrew L. Kavee; Brad Wheeler; Bonnie E. Shook-Sa; Erika Samoff; David L. Rosen (PLoS ONE, 2025)
Objectives To enumerate and describe the population of people with HIV (PWH) with criminal charges and to estimate associations between charges and HIV outcomes. We hypothesized that being charged in the court system will be associated with declines in viral suppression. Methods We linked statewide North Carolina (NC) criminal court records to confidential HIV records (both 2017-2020) to identify a population of defendants with diagnosed HIV. We used generalized estimating equations to examine changes in viral suppression (outcome) in the time 12-month periods pre- and post-criminal charges (exposure), adjusting for other demographic and legal system factors. Results 9,534 PWH experienced criminal charges. Compared to others with charges, PWH were more likely to be male and report Black race. The median duration of unresolved charges was longer for PWH. A slightly larger proportion of PWH experienced viral suppression in the 12-month post-charge period compared to the pre-charge period (72% vs 70%, p < 0.05). Similarly, when adjusting for demographic factors, the 12-month period following resolution of charges was modestly associated with an increased likelihood of viral suppression (aRR 1.03, 95% confidence interval [CI] 1.02-1.04) compared to the pre-charge period. Conclusions A significant portion of PWH in NC had criminal charges during a three-year period, and these charges went unresolved for a longer time than those without HIV. There was a modest statewide increase in viral suppression in the 12-month period after resolution of charges. Considering the exploratory nature of study, the modest association between charges and viral suppression should not be interpreted causally. In contrast to our expectation, we did not find any evidence that charges were associated with a decline in viral suppression. We suggest future lines of research to improve upon this exploratory analysis and area of study.